Implementation of Google Docs Based Learning in Academic Writing class - Muhammad Akbar; Muhammad Basri; Muhammad Tahir (International Journal of Language, Education, and Literature, 2025)
This research explored Google Docs based learning in teaching academic writing at Indonesian Higher Education. The objective of this research is to find out the implementation of Google Docs based learning in teaching writing skills at Indonesian Higher Education. This research used a purposive sampling technique to get data. The subjects of this research were one lecturer and five students from STKIP YPUP Makassar. The data resource of this research was collected through an observation checklist in the classroom and semi-structured interviews with the lecturer and students. The result showed that, the implementation of Google Docs in Indonesian Higher Education enhances collaboration and real-time interaction in academic writing. Google Docs is Highly implemented to enhances collaboration and real-time interaction, with a few implemented Google Docs in Moderately and Low implementation. To optimize Google Docs, students should actively use this platform, Lectures should provide comprehensive tutorials, University must ensure reliable curriculum and internet and other researcher should further explore on diverse learning outcomes.